2022
DOI: 10.1155/2022/1554875
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat: A New Hope for Heart Failure Patients

Abstract: Heart failure with reduced ejection fraction (HFrEF) is the inability of the heart to adequately contract or eject blood. This heart is unable to produce adequate cardiac output to perfuse vital tissues. At a fundamental level, it is known that the cardioprotective pathway of nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate is impaired in heart failure patients. Vericiguat is a novel, orally used, small molecule, and direct stimulator of the soluble guanylate cyclase, and thus, it enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Elevated levels of cGMP have been associated with improved cardiac contractility [39], as the heart muscle can contract more forcefully and pump blood more effectively. Thus, vericiguat reduces cardiac hypertrophy, which is the thickening of the heart muscle due to chronic pressure overload [40]. By reducing hypertrophy, vericiguat may help to prevent or reverse the pathologic structural remodeling of the heart, leading to improved heart function.…”
Section: Mechanism Of Action Of Vericiguatmentioning
confidence: 99%
“…Elevated levels of cGMP have been associated with improved cardiac contractility [39], as the heart muscle can contract more forcefully and pump blood more effectively. Thus, vericiguat reduces cardiac hypertrophy, which is the thickening of the heart muscle due to chronic pressure overload [40]. By reducing hypertrophy, vericiguat may help to prevent or reverse the pathologic structural remodeling of the heart, leading to improved heart function.…”
Section: Mechanism Of Action Of Vericiguatmentioning
confidence: 99%
“…A growing body of preclinical and clinical evidence revealed that the stimulation of the nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate (NO-sGC-cGMP) pathway by sGC stimulators represents a potential therapeutic approach for the management of HF [ 9 ]. The sGC enzyme is an intracellular nitric oxide (NO) receptor that catalyzes the synthesis of the second messenger cyclic guanosine monophosphate (cGMP), when activated [ 10 ].…”
Section: An Overview Of Vericiguatmentioning
confidence: 99%
“…The median follow-up for the primary endpoint was 11 months. The annualized absolute risk reduction with the drug treatment was ~4.2% over the course of the study [148]. The recommended initial oral dose of vericiguat was 2.5 mg/day, with food intake, and should be doubled approximately every 2 weeks to reach the target maintenance dose of 10 mg/day.…”
Section: Drug Targeting Of Mitochondrial Ca 2+ and Homeostasismentioning
confidence: 99%